The Impact of a Comprehensive Intervention on Sensorimotor Recovery in Cerebro Vascular Accident (CVA) Patients in Selected Hospitals, Coimbatore, Tamil Nadu - Deepa Ramaswamy; Arockiamary Ignasimuthu; S. Parimala; Lingaraj Chitra; Sasikala Gunasekaran; Panneerselvam Periasamy (Journal of Pharmacy and Bioallied Sciences, 2025)
Introduction: A cerebrovascular accident (CVA) occurs when a blood clot blocks oxygen and blood flow to the brain, causing physical limitations, sensory dysfunction, headaches, and incontinence in patients. This study explores the impact of an interventional package on sensorimotor function in CVA patients. Material and Methods: A study was conducted to assess the effect of an interventional package on sensorimotor function among chronic venous artery disease CVA patients at various hospitals in Coimbatore. The study involved a quasi-experimental design, pretest and posttest with a control group, and a quantitative approach. The study involved 300 CVA patients selected through a multistage random sampling technique, and their sensorimotor function, headache intensity, and urinary incontinence were evaluated using the Fugl-Meyer assessment and NPRS. Results: The study analyzed the demographics of stroke patients over 55 years old, focusing on males (66% and 58.67%) and females (34% and 41.33%). The majority of patients were married (81.33% and 75.33%) and were both smokers and alcoholics (52% and 42%). Most patients developed diabetes mellitus, and 30.67% and 37.33% had comorbidities for over 20 years. Menopausal women made up the highest percentages (26.67% and 33.33%). Clinical factors showed that the largest and most comparable percentages (84% and 79.33%) had no prior history of stroke hospitalization. All patients with ischemic stroke showed paralysis in both limbs, with the greatest and most similar percentages (56% and 58%) showing right lateralization of the lesion and weakening of the left side of the limbs. Conclusion: The interventional package successfully improved sensorimotor function, reduced headache frequency, and reduced urine incontinence in CVA patients, with no significant difference in pretest and posttest results. Demographic factors and clinical characteristics were associated with these improvements.